CSR and Its Impacts on Society during Pandemic Covid-19: Evidence from Bali as a Tourist Destination - Putu Indah Rahmawati (Universitas Pendidikan Ganesha, 2023)
The emerging body of literature has indicated the positive impact of CSR on society and the environment. However, our understanding of how CSR can support society's resilience in facing crises during the COVID-19 pandemic still needs to be improved. This research focused on answering the following questions about corporate social responsibility to what extent does corporate social responsibility contribute to society in Bali, and how does CSR implement in Bali? This research takes a qualitative case study approach. Data were analyzed by content analysis to the official websites of the top 100 companies in Indonesia in 2020. The findings reveal that CSR has a significant contribution to society in Bali. CSR was implemented in various ways and recipients all over Bali island. Some companies distributed the CSR directly to the communities, and some were collected through local government and then distributed based on a government's list of recipients. There has been good collaboration between industry and government in distributing CSR funds in Bali. The majority of CSR was given in the form of giving free groceries and masks for the poor, personal safety equipment for health workers, and sinks for washing hands in public spaces such as markets, temples, and shops.